Community empowerment in the use of family medicinal plants (TOGA) - Nur Rahmi Hidayati; Kelvin Muhaerin; Indah Mutia Sari; Oktavia Dwi Chahyani; Lilis Listiyani; Puspita Afriliani; Lika Latifatul Amanah; Ismatul Laila; Diva Fadllan Nur Setiawan; Rania Nur Ainun (Community Empowerment, 2023)
Family medicinal plants (TOGA) offer a safe alternative treatment option since they rarely cause side effects, are easy to process and consume, and are relatively inexpensive. However, the residents of Bode Lor Village in Plumbon District, Cirebon Regency, prefer chemical drugs for their daily treatments. The objective of this community service initiative is to impart knowledge about the benefits of traditional medicinal plants and promote the cultivation of family medicinal plants (TOGA). The methods employed in this program encompass observation, outreach, counseling, and training in the preparation of infused water and instant granules, offering an alternative to traditional medicine that can be sold, marketed, and hold economic value. The program's results demonstrated an increase in residents' knowledge regarding the benefits of traditional medicine and raised awareness about planting medicinal plants around their homes. This also included an improvement in their skills in utilizing TOGA through the creation of infused water and instant granulated ginger, ultimately contributing to increased family income.